Blockchain: A Coordination Mechanism - Lesław Pietrewicz (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
Blockchain technology is firmly established in the public awareness as a revolutionary new technology underpinning cryptocurrency. However, its potential applications can be found across sectors and industries in providing a novel way of producing coordination necessary to transact online, making it a timely invention in the age of progressing digitalization and increasing demands for efficiency and security of online transactions, and a promising research topic addressing the growing academic interest in the coordination aspect of the contract scholarship. The aim of this conceptual paper is to model blockchain as a coordination mechanism for online transactions. Three key aspects of coordination with blockchains are identified and examined – (1) producing consensus about the facts relevant to a transaction, (2) coding contracts, and (3) autonomously executing transactions. They are argued to be integral parts of the mechanism, jointly enabling blockchains to function as a complete mechanism of coordination for online transactions. The model is intended to inform debates on the prospects for the blockchain technology and can be further used to integrate coordination and contract scholarship.
Keywords: D23; D26; D86; L14; L23; L86; M11; 330; algorithmic coordination; blockchain; consensus; contract; coordination mechanism